ANALISIS PENERAPAN KEBIJAKAN EKONOMI SOSIALIS VENEZUELA PADA MASA PEMERINTAHAN HUGO CHAVEZ MENGHADAPI IMPERIALISME EKONOMI AMERIKA SERIKAT TAHUN 1998-2013 - Rino Razali (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2014)
This describes through analysis of the literature study on the application of the socialist economy in Venezuela when leadership of Hugo Chavvez. This Research intended to analyse the application of Venezuela socialist economic policies when the leadreship of Hugo Chavez to face the Economic imperialism by United States of America in 1998-2013. It is because the US economic imperialism was very detrimental to the people of venezuela.Keywords: policy, bolivarianisme, economics.